2005
DOI: 10.1109/tvt.2004.838890
|View full text |Cite
|
Sign up to set email alerts
|

Solutions to Performance Problems in VoIP Over a 802.11 Wireless LAN

Abstract: Voice over Internet Protocol (VoIP) over a wireless local area network (WLAN) is poised to become an important Internet application. However, two major technical problems that stand in the way are: 1) low VoIP capacity in WLAN and 2) unacceptable VoIP performance in the presence of coexisting traffic from other applications. With each VoIP stream typically requiring less than 10 kb/s, an 802.11b WLAN operated at 11 Mb/s could in principle support more than 500 VoIP sessions. In actuality, no more than a few se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
148
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(154 citation statements)
references
References 20 publications
2
148
0
1
Order By: Relevance
“…Moreover, they have to operate in the presence of unintentional spurious signals from electronic devices that either use this band, like cordless phones, microwave ovens, baby monitors, security cameras, or operate in adjacent frequency bands, like a number of wireless appliances whose distribution in modern houses, public and professional contexts is by now widespread. Some authors tried to investigate on the effects of interference on voice quality in a VoWLAN conversation (Wang & Mellor, 2004;Wang & Li, 2005;Garg & Cappes, 2002;El-fishawy et al, 2007;Prasat, 1999;Hiraguri et al, 2002). For instance, in (Wang & Li, 2005) the coexistence of Transmission Control Protocol (TCP) and VoIP traffic in a WLAN has been studied in terms of delays and performance loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they have to operate in the presence of unintentional spurious signals from electronic devices that either use this band, like cordless phones, microwave ovens, baby monitors, security cameras, or operate in adjacent frequency bands, like a number of wireless appliances whose distribution in modern houses, public and professional contexts is by now widespread. Some authors tried to investigate on the effects of interference on voice quality in a VoWLAN conversation (Wang & Mellor, 2004;Wang & Li, 2005;Garg & Cappes, 2002;El-fishawy et al, 2007;Prasat, 1999;Hiraguri et al, 2002). For instance, in (Wang & Li, 2005) the coexistence of Transmission Control Protocol (TCP) and VoIP traffic in a WLAN has been studied in terms of delays and performance loss.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors tried to investigate on the effects of interference on voice quality in a VoWLAN conversation (Wang & Mellor, 2004;Wang & Li, 2005;Garg & Cappes, 2002;El-fishawy et al, 2007;Prasat, 1999;Hiraguri et al, 2002). For instance, in (Wang & Li, 2005) the coexistence of Transmission Control Protocol (TCP) and VoIP traffic in a WLAN has been studied in terms of delays and performance loss. In (Garg & Cappes, 2003), experimental studies have been shown on the throughput of IEEE 802.11b wireless networks for user diagram protocol (UDP) and VoIP traffic.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in practice, the VoIP capacity of WLANs is very low. For example, Wang et al [1] showed that IEEE 802.11b and 802.11g WLANs are only able to support 12 and 60 VoIP sessions respectively. The main reason is the high overheads associated with the transmission of small VoIP packets.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, the constant bit rate nature of VoIP sessions exacerbates collisions, which in turn causes the Rate Adaptation Algorithm (RAA) at the sender to transmit at a lower data rate. As a solution, the authors of [1] propose to combine small VoIP packets and multicasts only one aggregated frame to stations, which has the affect of increasing VoIP capacity by 100%. This solution, however, considers all stations to be awake at all times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation